(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores the complexities and challenges of language testing and assessment in multi-level groups, where students with varying proficiency levels are assessed together. It identifies key issues such as the difficulty in creating fair and reliable tests, the varying levels of proficiency, concerns over test validity, the risk of cultural and linguistic bias, and the impact of test anxiety and motivation. The article also addresses the constraints on time for assessing students individually and discusses the balance between formative (assessment for learning) and summative (assessment of learning) assessments. It concludes by suggesting solutions such as differentiated assessments, the use of multiple assessment formats, peer and self-assessment, and a focus on ongoing feedback to improve the fairness and effectiveness of language testing in multi-level classrooms. By addressing these challenges, the article aims to help educators design assessments that are both equitable and effective in diverse classroom settings.